2014
DOI: 10.1186/s12934-014-0167-3
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the recombinant protein quality in Lactococcus lactis

Abstract: BackgroundEscherichia coli has been a main host for the production of recombinant proteins of biomedical interest, but conformational stress responses impose severe bottlenecks that impair the production of soluble, proteolytically stable versions of many protein species. In this context, emerging Generally Recognized As Safe (GRAS) bacterial hosts provide alternatives as cell factories for recombinant protein production, in which limitations associated to the use of Gram-negative microorganisms might result m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
2
21
0
1
Order By: Relevance
“…They described that under the overexpression of a fluorescent protein, highly fluorescent protein clusters are formed in Lactococcus lactis cytoplasm [18]. In this line, our group confirmed the presence of protein deposits in L. lactis cytoplasm using a modified green fluorescent protein [19]. The consideration of all these results together, lead us to believe that L. lactis might potentially be used for the generation of fully safe proteinbased particles that could be further explored as functional nanomaterials.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…They described that under the overexpression of a fluorescent protein, highly fluorescent protein clusters are formed in Lactococcus lactis cytoplasm [18]. In this line, our group confirmed the presence of protein deposits in L. lactis cytoplasm using a modified green fluorescent protein [19]. The consideration of all these results together, lead us to believe that L. lactis might potentially be used for the generation of fully safe proteinbased particles that could be further explored as functional nanomaterials.…”
Section: Introductionsupporting
confidence: 69%
“…The electroporation mix was centrifuged for 10 min at 10,000Âg at 4°C and the pellet was resuspended in 100-200 lL of M17 media and plated. Besides, recombinant Green Fluorescent Protein (rGFP) previously described in [19,26] were also used.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…These Gram-positive bacteria are non-pathogenic and non-invasive and inhabit different ecological niches (plant surfaces and the digestive tract of animals and human) 3 4, 5, 6, 7. Antigens delivered by recombinant LAB at the mucosal site would avoid the massive degradation of the antigens observed in the gut when purified antigens are used.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of USP45 signal peptide was reported to vary dependent on the nature of the expressed protein and culture conditions (Dieye et al ; Hazebrouck et al ; Siaw et al ). Cano‐Garrido et al () reported the solubility of aggregation‐prone GFP variant (VP1GFP), expressed using pNZ8148 in L. lactis , was influenced by time, culture conditions and growth temperature, which have a dramatic effect not only on protein yield but also on protein solubility and conformational quality that were particularly favoured under fermentative anaerobic metabolism. Despite testing an extended duration of expression (6–12 h) at different growth temperatures (including the optimum 30°C), as previously reported for secretion of recombinant proteins containing USP45 (Subramaniam et al ; Siaw et al ), the expressed recombinant S‐Ara2.02‐H remained insoluble and intracellular even after 24 h of expression.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of USP45 signal peptide was reported to vary dependent on the nature of the expressed protein and culture conditions (Dieye et al 2003;Hazebrouck et al 2007;Siaw et al 2016). Cano-Garrido et al (2014) reported the solubility of aggregation-prone GFP variant (VP1GFP), expressed using pNZ8148 in L. lactis, was Figure 3 Recombinant S-Ara2.02-H, rAra h 2.02 and nAra h 2 native peanut allergen showed comparable reactivity to serum IgE. A total of 5 µg ml À1 of the respective allergens were used to coat a 96-well microtitre plate for ELISA assay, using pooled sera from peanut allergic mice ( ) and biotinylated anti-mouse IgE for detection.…”
Section: Discussionmentioning
confidence: 99%